Development of a m6A- and ferroptosis-related LncRNA signature for forecasting prognosis and treatment response in cervical cancer - Kaiting Wen; Lili Wang; Huancheng Su; Lijun Yu; Sanyuan Zhang; Meiyan Wei; Yaling Wang; Le Zhao; Yan Guo (BMC Cancer)
Abstract Background N6-methyladenosine (m6A) and ferroptosis are involved in the development and prognosis of various cancers via long noncoding RNAs (lncRNAs). This study aimed to investigate the cervical cancer subtypes based on m6A-and ferroptosis-related lncRNAs (mfrlncRNAs) and to construct a mfrlncRNA signature to predict cervical cancer prognosis and treatment response. Methods mfrlncRNA-related cervical cancer subtypes were identified based on public datasets, and their differences in terms of prognosis, immune cell infiltration, and biological mechanisms were compared. Moreover, prognosis-related mfrlncRNAs were identified to construct a prognostic signature. A nomogram was constructed based on the independent prognostic factors. Immune characteristics, immunotherapy response predictions, and drug sensitivity analyses were performed for both risk groups. Furthermore, quantitative PCR was performed to validate the differential expression of the signature mfrlncRNAs in clinical samples. Results In total, 549 differentially expressed mfrlncRNAs were identified between cervical cancer and normal samples. Two mfrlncRNA-related cervical cancer subtypes that exhibited distinct prognoses, immune characteristics, and biological mechanisms were identified. A prognostic signature was developed using six prognostic mfrlncRNAs: AC016065.1, AC096992.2, AC119427.1, AC133644.1, AL121944.1, and FOXD1_AS1. This prognostic signature exhibited high performance in predicting the prognosis of cervical cancer. Moreover, RiskScore and stage were identified as independent prognostic factors, and a nomogram was constructed to accurately forecast overall survival. Furthermore, patients in the low-risk group had a more active immunotherapy response and were more sensitive to chemotherapeutic drugs such as imatinib. Upregulated expression of AC119427.1, AC133644.1, AL121944.1, and FOXD1_AS1 was observed in the tumor samples. Conclusions The six-mfrlncRNA signature is a new biomarker for forecasting prognosis and treatment response in cervical cancer.